2005
DOI: 10.1211/jpp.57.12.0001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological actions of Cordyceps, a prized folk medicine

Abstract: Cordyceps species, including C. sinensis, C. militaris, C. pruinosa and C. ophioglossoides, are prized traditional medicinal materials. The aim of this article is to review the chemical constituents and pharmacological actions of Cordyceps species. The chemical constituents include cordycepin (3 0 -deoxyadenosine) and its derivatives, ergosterol, polysaccharides, a glycoprotein and peptides containing -aminoisobutyric acid. They include anti-tumour, anti-metastatic, immunomodulatory, antioxidant, anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
183
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(188 citation statements)
references
References 104 publications
0
183
0
5
Order By: Relevance
“…Traditional Chinese medicine believes that C. militaris can be used to treat impotence, seminal emission, and infertility, and invigorate kidney and lungs [Ch 2000;Zhu et al 1998]. Pharmacological studies have confirmed that C. militaris possesses a wide range of biological activities including anti-bacterial, anti-tumor, anti-oxidation, and immune-modulatory [Liu et al 1994;Ng and Wang 2005;Reis et al 2013]. It can also improve reproductive function and repair reproductive dysfunction induced by cyclophosphamide in mice [Jin and Chen 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine believes that C. militaris can be used to treat impotence, seminal emission, and infertility, and invigorate kidney and lungs [Ch 2000;Zhu et al 1998]. Pharmacological studies have confirmed that C. militaris possesses a wide range of biological activities including anti-bacterial, anti-tumor, anti-oxidation, and immune-modulatory [Liu et al 1994;Ng and Wang 2005;Reis et al 2013]. It can also improve reproductive function and repair reproductive dysfunction induced by cyclophosphamide in mice [Jin and Chen 2008].…”
Section: Introductionmentioning
confidence: 99%
“…These entomopathogenic fungi have a wide spectrum of pharmacological activities (Ng & Wang, 2005). It shows antioxidant, anti-inflammatory, antitumor, antiociceptive, antifibrotic and antiangiogenic activities (Ng & Wang, 2005), and immunopotentiation properties (Kuoet al, 2007). C. militaris was reported to improve insulin resistance and insulin secretion (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of erythropoiesis has been reported as well as well as antibacterial, anti-fungal and anti-microbial activity (Ng and Wang, 2005).…”
Section: Other Effectsmentioning
confidence: 99%